Women living with psoriasis : a phenomenological study - Glynn, Erin Imelda, 1969- (2008)
Thesis (M.N.)--Memorial University of Newfoundland, 2008. Nursing Includes bibliographical references (leaves 78-83) Psoriasis is a chronic condition of the skin for which there is no cure. There are over 1 million people in Canada with psoriasis and it is estimated that 2-3% of the population of Newfoundland and Labrador are sufferers. The lived experience is important for people suffering with psoriasis and encompasses more than treatment modalities. The clinical manifestations, diagnosis and treatment, physical and psychosocial effects of psoriasis, and quality of life issues have been covered in the current literature. Little research has been conducted on the lived experience of individuals with psoriasis. By using phenomenology as a research method, the lived experience of four women living with psoriasis in Newfoundland is explored. The analysis reveals the themes from the lived experience of these women. These themes are: 1) More than just a rash - physical symptoms; 2) Understanding from others - support; 3) Creative clothing - covering up; 4) The good, the bad, and the scary - treatment options; 5) Looking for answers; 6) Managing the public gaze - avoidance; 7) Knowing triggers - observing patterns; and 8) Moving on - developing comfort. It is hoped that nurses and other health care professionals will gain a better understanding of the lived experience of these women and be better able to provide holistic care to those suffering from psoriasis.